'Subordination' versus 'coordination' in sentence and text: a cross-linguistic perspective - Fabricius-Hansen, Cathrine; Ramm, Wiebke (J. Benjamins Pub. Co, 2008)
The papers collected in this volume (including a comprehensive introduction) investigate semantic and discourse-related aspects of subordination and coordination, in particular the relationship between subordination/coordination at the sentence level and subordination/coordination - or hierarchical/non-hierarchical organization - at the discourse level. The contributions in part I are concerned with central theoretical questions; part II consists of corpus-based cross-linguistic studies of clause combining and discourse structure, involving at least two of the languages English, German, Dutch
Includes bibliographical references and indexes. - Description based on print version record
Keywords: Electronic books; Aufsatzsammlung; Koordination; Hypotaxe; Syntax; Kontrastive Linguistik